2013
DOI: 10.2753/mer1052-8008230109
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Group Marketing Presentations: A Modified Pecha Kucha Approach

Abstract: ImprovIng Student group marketIng preSentatIonS: a modIfIed pecha kucha approach Jason oliver and christine kowalczykStudent presentations can often seem like a formality rather than a lesson in representing oneself or group in a professional manner. To improve the quality of group presentations, the authors modified the popular presentation style of Pecha Kucha (20 slides, 20 seconds per slide) for marketing courses to help students prepare and deliver professional business presentations. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
9
0
2
Order By: Relevance
“…From the need for storytelling to reach diverse audiences and sell ideas (Barker & Gower, 2010;Nishi, 2013), to the use of visual images to increase listeners' attention and recall of information (Kernbach, Eppler, & Bresciani, 2014), to the need to be concise in an age of shrinking attention spans (Evans, 2014), PechaKucha presentations can prepare students for those demands. Not only does research indicate that students' demonstrated communication competence is as strong or stronger in PechaKucha presentations as it is with traditional speaking styles (Beyer, 2011;Oliver & Kowalczyk, 2013), but students also view these presentations as "fun." Yet, PechaKucha presentations are not nearly as widespread as one might imagineperhaps because there is little pedagogical guidance available.…”
mentioning
confidence: 93%
“…From the need for storytelling to reach diverse audiences and sell ideas (Barker & Gower, 2010;Nishi, 2013), to the use of visual images to increase listeners' attention and recall of information (Kernbach, Eppler, & Bresciani, 2014), to the need to be concise in an age of shrinking attention spans (Evans, 2014), PechaKucha presentations can prepare students for those demands. Not only does research indicate that students' demonstrated communication competence is as strong or stronger in PechaKucha presentations as it is with traditional speaking styles (Beyer, 2011;Oliver & Kowalczyk, 2013), but students also view these presentations as "fun." Yet, PechaKucha presentations are not nearly as widespread as one might imagineperhaps because there is little pedagogical guidance available.…”
mentioning
confidence: 93%
“…Sind die Forschungen zu Sprachlernkontexten vor allem an Sprachproduktionsaspekten interessiert, nehmen andere Studien eher die Rezeption in den Blick und fragen zum Beispiel nach den Verstehens-und Behaltensleistungen bei Pecha Kucha im Vergleich zu herkömmlichen PowerPoint-Präsentationen [10] sowie nach verschiedenen Qualitätsurteilen.…”
Section: Was Ist Pecha Kucha?unclassified
“…Gemessen an klassischen und auch in den meisten Leitfäden erwähnten Kriterien für gelungene Referate wie klare Vortragsstruktur oder Blickkontakt schneiden Pecha-Kucha-Vorträge besser ab [11]. Auch wenn es keine eindeutigen Belege dafür gibt, dass Pecha-Kucha-Präsentationen deshalb generell besser als andere Präsentationsformate dazu geeignet sind, um fachliche Inhalte zu verstehen und zu behalten [10], werden sie von Studierenden wie auch Dozierenden doch häufig als subjektiv angenehmer und vor allem unterhaltsamer wahrgenommen [12].…”
Section: Was Ist Pecha Kucha?unclassified
“…Slides should only consist of an image and perhaps a few words. Research has shown that the Pecha Kucha presentation is connected to improved academic performance and confidence when compared to traditional presentations (Oliver & Kowalczyk, 2013). Faculty modeled this practice on the first day of the institute and students presented on the final day of the institute.…”
Section: Summer Institutementioning
confidence: 99%